Self‐powered technology based on nanogenerators for biomedical applications - Yuanzheng Zhang (Exploration, 2021)
Abstract Biomedical electronic devices have enormous benefits for healthcare and quality of life. Still, the long‐term working of those devices remains a great challenge due to the short life and large volume of conventional batteries. Since the nanogenerators (NGs) invention, they have been widely used to convert various ambient mechanical energy sources into electrical energy. The self‐powered technology based on NGs is dedicated to harvesting ambient energy to supply electronic devices, which is an effective pathway to conquer the energy insufficiency of biomedical electronic devices. With the aid of this technology, it is expected to develop self‐powered biomedical electronic devices with advanced features and distinctive functions. The goal of this review is to summarize the existing self‐powered technologies based on NGs and then review the applications based on self‐powered technologies in the biomedical field during their rapid development in recent years, including two main directions. The first is the NGs as independent sensors to converts biomechanical energy and heat energy into electrical signals to reflect health information. The second direction is to use the electrical energy produced by NGs to stimulate biological tissues or powering biomedical devices for achieving the purpose of medical application. Eventually, we have analyzed and discussed the remaining challenges and perspectives of the field. We believe that the self‐powered technology based on NGs would advance the development of modern biomedical electronic devices.